Executive Function Buffers the Association between Early Math and Later Academic Skills - Ribner, Andrew D.; Willoughby, Michael T.; Blair, Clancy B.; , The Family Life Project Key Investigators (Frontiers in Psychology, 2017)
Extensive evidence has suggested that early academic skills are a robust indicator of later academic achievement; however, there is mixed evidence of the effectiveness of intervention on academic skills in early years to improve later outcomes. As such, it is clear there are other contributing factors to the development of academic skills. The present study tests the role of executive function (a construct made up of skills complicit in the achievement of goal-directed tasks) in predicting 5th grade math and reading ability above and beyond math and reading ability prior to school entry, and net of other cognitive covariates including processing speed, vocabulary, and IQ. Using a longitudinal dataset of N = 1292 participants representative of rural areas in two distinctive geographical parts of the United States, the present investigation finds executive function at age 5 strongly predicts 5th grade academic skills, as do cognitive covariates. Additionally, investigation of an interaction between early math ability and executive function reveals the magnitude of the association between early math and later math varies as a function of early EF, such that participants who have high levels of executive function can “catch up” to peers who perform better on assessments of early math ability. These results suggest executive function is pivotal to the development of academic skills throughout elementary school. Implications for further research and practice are discussed.